2002
DOI: 10.1176/appi.ps.53.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Medication Regimens and Participation in Dual-Focus Self-Help Groups

Abstract: Objective-The authors examined the associations between attendance at self-help meetings, adherence to psychiatric medication regimens, and mental health outcomes among members of a 12-step self-help organization specifically designed for persons with both chronic mental illness and a substance use disorder.Methods-A sample of members of Double Trouble in Recovery (DTR) was interviewed at baseline and one year later. Correlates of adherence to psychiatric medication regimens at the followup interview were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 35 publications
2
66
0
5
Order By: Relevance
“…It is also seen that having someone to give medication on time or monitoring medications may have influence in compliance behavior and more likely to be adherent than those who lived without such support. 6 In this study quality of interaction with health professional is significantly associated with the level of compliance (P<0.05). A positive relationship with the therapist influenced much to patient's medication compliance.…”
Section: Lama S Et Al May-august 2012; Vol 10 (No2);113-117mentioning
confidence: 49%
See 2 more Smart Citations
“…It is also seen that having someone to give medication on time or monitoring medications may have influence in compliance behavior and more likely to be adherent than those who lived without such support. 6 In this study quality of interaction with health professional is significantly associated with the level of compliance (P<0.05). A positive relationship with the therapist influenced much to patient's medication compliance.…”
Section: Lama S Et Al May-august 2012; Vol 10 (No2);113-117mentioning
confidence: 49%
“…Majority (78.0%) of the respondents had no family history of mental illness & 94.7% respondents visited the hospital for regular follow up visit. (Table 2: Clinical Characteristics of subjects) 6 Although antipsychotic medications have been shown to improve psychopathology, reduce relapse, & improve functioning non-adherence to treatment with antipsychotic is common. Improving adherence to treatment with antipsychotic medication in patients with psychotic disorders is a challenging task.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in attendance and level of participation may account for differences in outcome, a phenomenon analogous to the "dose-response" relationship in pharmacology. Several studies in the current review reported a correlation between higher levels Mutual help groups, p.19 of participation or involvement (operationalized in various ways) and positive outcomes (Caserta & Lund, 1993;Houston et al, 2002;Lieberman & Videka-Sherman, 1985;Magura et al, 2002).…”
Section: Mutual Help Groups P18mentioning
confidence: 66%
“…Individuals who participated in more dual diagnosis services and 12-Step self-help groups showed slightly more gains in their use of problem-centered coping skills. A cross-sectional study also supported that the degree of participation in dualfocus (mental illness and addiction) self-help groups was significantly associated with degree of medication adherence (Magura, Laudet, Mahmood, Rosenblum, & Knight, 2002). Another prospective study (Lecomte et al, 1999) found that persons with severe mental illness participating in a 12-week treatment program geared toward improving self-esteem improved in active coping skills, in contrast with participants receiving treatment as usual.…”
Section: Transitory/episodic Experiences and Copingmentioning
confidence: 87%